Correlation of neutrophil-to-lymphocyte ratio and clinical outcome of acute thrombotic stroke in patients with COVID-19 - Sarengat, Rizky; Islam, Mohammad S.; Ardhi, Mohammad S. (Narra J, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has caused millions of deaths worldwide. Acute ischemic stroke is a life-threatening risk factor for COVID-19 infection. Neutrophil-to-lymphocyte ratio (NLR) is one of the predictors of poor prognosis in acute ischemic stroke. The aim of this study was to assess the correlation between NLR values and the clinical outcome of acute thrombotic stroke patients with COVID-19 that was measured using the National Institutes of Health Stroke Scale (NIHSS). A cross-sectional hospital-based study was conducted in Dr. Soetomo General Hospital Surabaya, Indonesia. Patients with acute thrombotic stroke and COVID-19 admitted between 1 March 2020 and 31 May 2021 were recruited. The NLR values and the NIHSS scores were assessed during the admission and the correlation between NLR and NIHSS scores was calculated. This study included 21 patients with acute thrombotic stroke and COVID-19, consisting of 12 males and 9 females. The mean age was 57.6 years old. The mean NLR values was 8.33±6.7 and the NIHSS scores ranging from 1 to 33. Our data suggested a positive correlation between NLR values and NIHSS scores, r=0.45 with p=0.041. In conclusion, the NLR value is potentially to be used as a predictor of the clinical outcome in acute thrombotic stroke patients with COVID-19. However, further study is warranted to validate this finding.